Think twice : harnessing the power of counterintuition - Mauboussin, Michael J., 1964- (Boston, Mass. : Harvard Business Press, 2009)
Leaders in business, medicine, law and government make crucial decisions every day. The harsh truth is that they mismanage many of those choices, even though they have the right intentions. Why is it so hard to make sound decisions? Mauboussin offers powerful rules for avoiding error.
Smart is as smart does -- The outside view : why Big Brown was a bad bet -- Open to options : how your telephone number can influence your decisions -- The expert squeeze : why Netflix knows more than clerks do about your favorite films -- Situational awareness : how accordion music boosts sales of burgundy -- More is different : how bees find the best hives without a real estate agent -- Evidence of circumstance : how outsourcing the Dreamliner became Boeing's nightmare -- Grand ah-whooms : how ten Brits made the Millennium Bridge wobble -- Sorting luck from skill : why investors excel at buying high and selling low -- Time to think twice : how you can change your decision making immediately.
Includes bibliographical references (pages [145]-178) and index.
Description based on print version record.
Keywords: Decision making; Decision making; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books